Learning and Teaching Ethics in Tafsir Al-Maraghi by Abd Al-Rahman Al-Maraghi - Cecep Anwar; Hafid; Azkia Fazri Nurhidayah; Sundari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In the educational process, of course, it cannot be separated from the teaching and learning process which requires interaction between teachers and students. In order to achieve the goal of Islamic education, namely to produce people who serve themselves to Allah SWT, it is necessary to have rules that accompany the interaction process between students and their teachers. Ethics in learning and teaching includes principles and values that teach about what is right and wrong. To explain this ethics, the main basis is Islamic ethics, which comes from the Al-Qur'an and As-Sunnah. Therefore, this research aims to explore the ethics of learning and teaching contained in the Al-Qur'an. This research discusses the ethics of teaching and learning according to the interpretation of Al-Maraghi Q.S An-Nahl: 125 and Q.s Al-Mujadilah verse 11. This research uses a qualitative approach and literature study as the analysis method. The research results show that the application of ethics in learning and teaching is a very important part of the learning process. Both educators and students involved in teaching and learning activities must respect each other and maintain ethics. Tafsir al-Maraghi, the work of a great scholar from Egypt, provides extensive insight into how to understand the Al-Qur'an in a social, political and cultural context. This journal examines the importance of ethics in learning and teaching tafsir, with a focus on thematic tafsir in the style of al-Maraghi. This research aims to identify the ethical values contained in al-Maraghi's tafsir.